Laboring for Rights: Unions and Sexual Diversity Across Nations - Forrest, Anne (Relations industrielles / Industrial Relations, 2001)
Laboring for Rights: Unions and Sexual Diversity Across Nations, edited by Gerald Hunt, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Sexuality; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z